(untitled) (Herald of Journalism, 2019)
Social media sharing has become a strong trend among Kazakhstani women. Selfies are not merely pictures of oneself but an individual expression of the imagined virtual personality of the person. They are a means for social media communication, which invites for public recognition, liking and flirting. The purpose of the research was to explore the selfie as a self-presentation. It focused on the compositional characteristics of selfies of Kazakhstani women against the basic photographic rules and criteria. The need and rationale for the research stemmed in the lack of sufficient scientific research on the selfie phenomenon in Kazakhstan. The research methods the exploratory study employed were a qualitative visual content analysis with preset descriptors a research literature methodology. The results indicated that the imple-mentation of the basic rules and principles for a successful selfie such as the Rule of Thirds, Eye-in-Centre Principle, light, distance, and angle is limited. The value of the research is twofold. First, it contributed to an understudied scientific field of visual communication with a focus on Kazakhstan. Second, it provided practical guidelines for taking appealing selfies either for personal use or promotion purposes.